Si Juan tamad ay naging kalabaw Juan tamad became a carabao - Vibiesca, Renato C.; Denso, Almar; Agarao, Rowen (Quezon City Lampara Publishing House, Inc., 2009)
"The farmers in our village are extremely industrious. They are comparable to their carabaos. On the other hand, Juan is extremely lazy and can never compare to a carabao. That is why he was called "Juan tamad." Would Juan become industrious if he became a real carabao? read in this story what good fortune and value Juan gains after his experience as a carbao."
Stories with moral values
Text in Filipino and English.
A joint publication with Precious Pages Corporation for Easy to Learn Books.
Keywords: Laziness -- Fiction; Carabao -- Fiction